X‐ray micro‐computed tomography analysis of accumulated corrosion products in deep‐water shipwrecks. Issue 11 (11th June 2019) - Albahri, Mohammed; Barifcani, Ahmed; Dwivedi, Deepak; Iglauer, Stefan; Lebedev, Maxim; MacLeod, Ian D.; Machuca, Laura L.
Abstract : Accumulated corrosion products from two different shipwrecks which had lain on the seabed (2.5 km depth) for 73 years were systematically analysed by three‐dimensional imaging at high resolution using X‐ray micro‐computed tomography. Complementary surface and chemical characterization experiments were conducted to identify the morphological structure of the corrosion products. Goethite was observed as the main corrosion phase found in both the wreck's corrosion products. However, other corrosion products such as silica, lepidocrocite, maghemite, magnetite, benyacarite, jarosite and amorphous materials were noticed using Fourier transform infrared spectroscopy, Raman spectroscopy and X‐ray diffraction. In addition, mineralized microbial structures were also observed as significant constituents of the corrosion products. However, there were significant differences between samples from the two shipwrecks including porosity, distribution and volume percent of the corrosion products components. The mechanism of different corrosion products formation was proposed and discussed in detail. Abstract : Accumulated corrosion products from two different shipwrecks which had lain on the seabed (2.5 km depth) for 73 years were systematically analysed by three‐dimensional imaging at high resolution using X‐ray micro‐computed tomography. Complementary surface and chemical characterization experiments were conducted to identify the morphological structure of the corrosion products.